Empowering MSMEs Through Digital Marketing to Increase Product Sales - R Dewi Pertiwi; Dewi Yolanda Putri; Wanda Laksniyunita (Abdimas Paspama, 2023)
Along with the development of information technology, digital marketing has become an important tool to help MSMEs overcome various challenges in marketing and expand market reach. This research aims to analyze the effect of empowering Micro, Small and Medium Enterprises (MSMEs) through digital marketing strategies in increasing product sales to the community in Kayuambon Village, Lembang District, West Bandung Regency. The research results show that the MSME empowerment program through digital marketing in Kayuambon Village is effective in increasing the knowledge and skills of MSME players. Through training that includes the use of social media, product photography, and digital marketing strategies, participants are able to increase the visibility and sales of their products. MSME players have become more confident and creative in utilizing digital technology for marketing. This program contributes positively to local economic growth, showing that digital marketing strategies are strategic steps to empower MSMEs in the digital era